Incorporation and Effect of Arachidonic Acid on the Growth of Human Myeloma Cell Lines - V. Desplat; C. Dulery; V. Praloran; Y. Denizot (Hindawi Limited, 1999)
The objectives of this work are to investigate the incorporation of arachidonic acid (AA) in the human myeloma cell lines OPM2, U266 and IM9, and to assess the effect of AA and lipoxygenase products of AA on their growth. The kinetics of acylation of [3H]AA indicates that myeloma cells incorporate AA into their membrane phospholipids and triglycerides. PLA2-treatment and base hydrolysis experiments confirm that [3H]AA is incorporated unmodified in U266, IM9 and OPM2 phospholipids, and is linked by an ester bond. Prelabeling-chase experiments indicate no trafficking of labeled AA among the various phospholipid species. Addition of AA and lipoxygenase products of AA (leukotriene B4 and C4, lipoxin A4 and B4, 12- and 15-hydroxyeicosatetraenoic acid) have no effect on U266, IM9 and OPM2 proliferation assessed by [3H]thymidine incorporation into DNA. In conclusion, while human myeloma cells readily incorporate AA in their membrane phospholipids and triglycerides, AA and lipoxygenase products are not important modulators of their proliferation.